Factors influencing service recovery in nursing services - Dayang Nor Sarina, Azzeni (2018)
Service recovery has been an important issue due to broader social and economic context that shows greater demand for health, care and support which conclude that it is critical to study the health care services. Predicting that factors such as top management leadership, teamwork, empowerment, training and commitment is critical to be understood because all this factors will affect the motivation and attitude of employees toward service recovery. Furthermore, employee is the only source of sustainable competitive advantage to organisations. Nursing staffs are the one who have variety of jobs to perform and need to juggle with many jobs at many place in the medical profession. Hence, there is no doubt that failure in their service might occur and service recovery is very crucial to make sure that nurses will perform better in service recovery. This study therefore aims to determine the factors influencing service recovery among public nurses. Nurse from public hospitals from various hospitals in Seberang Perai Utara, Pulau Pinang were chosen as respondents for this study. A total number of 400 questionnaires are distributed to respondents using simple random sampling method. Only 368 questionnaires were returned and being used for analysis. The results of correlation analysis and regression analysis both have shown that three independent variables (empowerment, training and commitment) have significant relationship and influenced towards service recovery. In conclusion, the finding in this study shows that nurse’s commitment is the most critical factors in service recovery.